WACANA KEMISKINAN DALAM PODCAST SISI GELAP ORANG MISKIN DI KANAL YOUTUBE TRETAN UNIVERSE: ANALISIS WACANA KRITIS TEUN A. VAN DIJK - Ibnu Syarofi, Muhammad; Saifudin, Windri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aimed to analyze the discourse construction of poverty in the podcast "Sisi Gelap Orang Miskin!" on the Tretan Universe YouTube channel through the dimensions of text structure, social cognition, and social context. A qualitative approach was employed using Teun A. van Dijk's Critical Discourse Analysis model, analyzing verbatim video transcripts and audience comments without direct interviews with the creators. The findings showed that the podcast constructed poverty as an inherited generational identity, while also criticizing social assistance policies deemed humiliating toward beneficiaries through verification mechanisms such as poverty household stickers. A paradox was also found in the use of social assistance cards, which were regarded as a lifeline on one hand, yet became instruments of debt collateral to loan sharks on the other. The discourse produced was ambivalent, containing both critique of structural failure and reproduction of individualizing narratives about the mentality of the poor. This study concluded that satirical humor in the podcast did not function solely as either stigma deconstruction or stigma reproduction, but instead presented both simultaneously within a single digital discursive space.